Relationship between self-control and peer conformity with smoking behavior - Fauzan Fauzan; Firman Firman; Daharnis Daharnis (Fakultas Ilmu Pendidikan UNP)
This research based on students of smoking behavior that unusual, smoking behavior is perceived as self-identity. However, students at senior high school level have great potential to be addicted to cigarettes.The low ability students in self-control and strength of peer conformity is the most dominant factor in influencing the smoking behavior of students. This study aims to describe self-control, peer conformity, smoking behavior, and the relationship of self-control andpeers conformity with smoking behavior. This research used quantitative approach with descriptive-correlational method. The subjects of this research were students which consume cigarette consists of 124 people. The instrument of the research, for all three variables was a Likert scale model, with instrument reliability:self-control 0.922, peers conformity 0.847, and smoking behavior 0.951. The data were analyzed by using multiple regression. The results shows that there was significant relationship between of self-control and peer conformity with smoking behavior.